School improvement and peer learning partnerships: building organizational resilience in primary schools in England - Godfrey, David; Munoz-Chereau, Bernardita (Frontiers in Education, 2024)
This article looks at organizational resilience (OR) through the analysis of a sub-set of data gained from an independent and embedded mixed methods implementation and process evaluation (IPE) of the Schools Partnership Programme (SPP) implemented over three years (2018)(2019)(2020)(2021) and funded by the Education Endowment Foundation (EEF) in England (Author 1 et al, 2023). A sample of 422 primary schools that took part in SPP (treatment schools) and their comparisons are analysed applying Duchek's (2020) organizational capability-based framework. We describe ways in which SPP 'learning map' addresses the i) anticipation, ii) coping and iii) adaptation stages and the extent to which SPP helped building organizational resilience. Taking this theoretical framework as a foundation is a novelty, as despite OR has become prominent in the academic literature (e.g., Vogus and Sutcliffe, 2007), apart from a few exceptions (e.g., Kopp and Pesti, 2022) there is a dearth of international research examining OR within the school sector. Drawing on SPP empirical data from numerous data collection strategies (interviews, surveys, shadowing school reviews and improvement workshops), the extent to which schools' resilience capacities were improved is analysed. Our findings suggest that SPP supported the development of OR in SPP primary schools. Despite facing several challenging external factors (student deprivation, the COVID disruption, changes to the external accountability framework and competing demands of other partner organisations) and internal factors (teacher attrition, need to developing leaders, upgrade pedagogical skills and encourage student subgroups who were underperforming) SPP schools exert 1) knowledge building through training, the review process, professional dialogue, learning from each other, as well as receiving and giving feedback. Regarding 2) resource availability, schools used SPP as a scaffold to build improvised strategies to access and mobilise shared human and physical resources; 3) social resources were built in the SPP through social capital, sharing of knowledge, enhancing a shared vision and trust. Finally, 4) SPP promoted lateral power dynamics driven by professional learning and accountability. Overall, the paper extends the understanding of school peer review approaches for school improvement (e.g. Author 1, 2020) and adds to the OR international literature by describing system resilience.